Association of baseline eGFR and incident heart failure on patients receiving intensive blood pressure treatment - Li Haonan; He Qiaorui; Zhu Wenqing; Zhang Yanjun; Pingcuo Wangjia; Yu Shikai; Deji Zhuoga; Zhang Yi; Zhao Yifan (ESC Heart Failure)
Abstract Aims We aim to elucidate the association of baseline eGFR and incident heart failure on patients receiving intensive BP treatment. Methods and results A post hoc analysis was conducted on the SPRINT database. Multivariab le Cox regression and interaction restricted cubic spline (RCS) analysis were performed to investigate the interaction between baseline eGFR and intensive BP control on heart failure prevention. The primary endpoint focused on incident heart failure. The study cohort comprised 8369 adults with a mean [SD] age of 68 [59–77] years, including 2940 women (35.1%). Over a median [IQR] follow‐up period of 3.9 [2.0–5.0] years, 183 heart failure events were recorded. A significant interaction was observed between baseline eGFR and treatment groups in terms of heart failure prevention (Interaction P = 0.012). The risk of heart failure showed a sharp slope until eGFR = 75 mL/min/1.73 m2 and then became flat by an interaction RCS. Intensive BP treatment did not exhibit a preventive effect on heart failure (HR (95% CI) = 1.03 (0.82–1.52)) when baseline eGFR was 75 mL/min/1.73 m2 or lower. Conversely, when baseline eGFR was higher than 75 mL/min/1.73 m2, a reduced risk of heart failure was observed (HR (95% CI) = 0.65 (0.41–0.98)). Intensive BP control did not increase the incident long‐term dialysis regardless of baseline eGFR but was associated with a higher risk of eGFR reduction. Conclusions Among nondiabetic hypertensive patients, baseline eGFR serves as a crucial indicator for assessing the risk reduction potential of intensive BP control in heart failure prevention, with 75 mL/min/1.73 m2 appearing as a suitable cut‐off value.